(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2022)
In this study an available reversed-phase HPLC method for the identification of sibutramine with UV detection and isocratic elution mode was developed, the evaluation of the method applicability and determination of validation indicators were carried out. It has been shown that the developed method meets the current international requirements. To search for sibutramine, the developed method has been used in some biologically active additives ("Lipocarnit", "Pineapple extract", "Turboslim night" and "Turboslim day").